A secondary battery and an electric device

CN122950474APending Publication Date: 2026-10-20CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611032570.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2021-11-11
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

本申请提供了一种二次电池和用电装置,二次电池包括负极极片,负极极片包括负极集流体、第一负极材料层和第二负极材料层,第一负极材料层位于负极集流体和第二负极材料层之间,第一负极材料层包括第一负极活性材料,第二负极材料层包括第二负极活性材料。本申请通过在负极集流体上设置第一负极材料层和第二负极材料层,并调控第一负极材料层中的第一负极活性材料,使得第一负极活性材料包括人造石墨A和人造石墨B,能够同时提高二次电池的能量密度和倍率性能,以及具有较长的使用寿命。当然,实施本申请的任一产品或方法并不一定需要同时达到以上所述的所有优点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This application provides a secondary battery and an electrical device. The secondary battery includes a negative electrode sheet, which comprises a negative current collector, a first negative electrode material layer, and a second negative electrode material layer. The first negative electrode material layer is located between the negative current collector and the second negative electrode material layer. The first negative electrode material layer includes a first negative electrode active material, and the second negative electrode material layer includes a second negative electrode active material. The first negative electrode active material includes artificial graphite A and artificial graphite B. Artificial graphite A comprises secondary particles and has an amorphous carbon coating layer on its surface. Artificial graphite B comprises primary particles and does not have an amorphous carbon coating layer on its surface. The first negative electrode active material and / or the second negative electrode active material comprises silicon-based materials. This design improves the rate performance of the secondary battery and provides a longer service life.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application based on the invention patent application with application number 202180094525.4, application date November 11, 2021, applicant CATL, entitled "A Secondary Battery and an Electric Device". Technical Field

[0002] This application relates to the field of electrochemistry, and in particular to a secondary battery and an electrical device. Background Technology

[0003] Rechargeable batteries, due to their advantages such as high energy density, long cycle life, and no memory effect, are widely used in wearable devices, smartphones, drones, electric vehicles, and large-scale energy storage devices, and have become the most promising new type of green chemical power source in the world today. However, this also places higher demands on the overall performance of rechargeable batteries, such as simultaneously possessing a long lifespan and good rate performance. Therefore, how to simultaneously achieve the desired lifespan and rate performance of rechargeable batteries has become an urgent problem to be solved. Summary of the Invention

[0004] This application is made in view of the above-mentioned issues, and its purpose is to improve the storage life and rate performance of secondary batteries at the same time.

[0005] To achieve the above objectives, this application provides a secondary battery and an electrical device.

[0006] A first aspect of this application provides a secondary battery comprising a negative electrode sheet, the negative electrode sheet comprising a negative current collector, a first negative electrode material layer, and a second negative electrode material layer, the first negative electrode material layer being located between the negative current collector and the second negative electrode material layer, the first negative electrode material layer comprising a first negative electrode active material, and the second negative electrode material layer comprising a second negative electrode active material, wherein the first negative electrode active material comprises artificial graphite A and artificial graphite B, the artificial graphite A comprising secondary particles and having an amorphous carbon coating layer on its surface, and the artificial graphite B comprising primary particles and not having an amorphous carbon coating layer on its surface.

[0007] Therefore, by setting a first negative electrode material layer and a second negative electrode material layer on the negative electrode current collector, and by adjusting the first negative electrode active material in the first negative electrode material layer so that the first negative electrode active material includes artificial graphite A and artificial graphite B, the rate performance of the secondary battery can be improved and the service life extended.

[0008] In any embodiment, the first negative electrode active material satisfies at least one of the following conditions: (1) the volume median particle size Dv50 is 13μm-18μm, optionally 15μm-16μm; (2) the particle size distribution satisfies 1≤(Dv90-Dv10) / Dv50≤1.6, optionally 1.1≤(Dv90-Dv10) / Dv50≤1.5; (3) the degree of graphitization is 92.8%-94.8%, optionally 93.5%-94.5%; (4) the specific surface area is 1.0 m². 2 / g-1.6 m 2 / g, can be selected as 1.05m 2 / g-1.3 m 2 / g; (5) The compacted density of the powder is 1.6g / cm³. 3 -1.85g / cm 3 1.7g / cm³ is an optional value. 3 -1.8g / cm 3 The first negative electrode active material satisfies at least one of the above conditions, which is beneficial to simultaneously improving the storage performance (e.g., extending storage life) and rate performance of the secondary battery.

[0009] In any embodiment, the artificial graphite A satisfies at least one of the following conditions: (1) the volume median particle size Dv50 is 14μm-20μm, optionally 16μm-18μm; (2) the particle size distribution satisfies 0.8≤(Dv90-Dv10) / Dv50≤1.7, optionally 0.9≤(Dv90-Dv10) / Dv50≤1.4; (3) the degree of graphitization is 91.0%-92.8%, optionally 91.5%-92.5%; (4) the specific surface area is 0.8 m². 2 / g-1.1 m 2 / g, optional 0.9m 2 / g-1m 2 / g; (5) The compacted density of the powder is 1.5g / cm³. 3 -1.8g / cm 3 The option is 1.6 g / cm³. 3 -1.8 g / cm 3 (6) Based on the mass of the first negative electrode active material, the mass percentage of the artificial graphite A is 10%-70%, optionally 30%-50%; (7) The mass ratio of the amorphous carbon coating layer in the artificial graphite A to the artificial graphite A is 1%-5%, optionally 3%-4%. The artificial graphite A satisfies at least one of the above conditions, which ensures storage life and is beneficial to improving the rate performance of the secondary battery.

[0010] In any embodiment, the artificial graphite B satisfies at least one of the following conditions: (1) the volume median particle size Dv50 is 12μm-16μm, optionally 15μm-16μm; the particle size distribution satisfies 0.5≤(Dv90-Dv10) / Dv50≤1.5; optionally, 0.7≤(Dv90-Dv10) / Dv50≤1.1; (2) the degree of graphitization is 93.5%-95.5%, optionally 94.0%-95.0%; (3) the specific surface area is 1.1m². 2 / g-1.6m 2 / g, can be selected as 1.3m 2 / g-1.5m 2 / g; (4) The compacted density of the powder is 1.6g / cm³. 3 -1.85g / cm 3 1.6g / cm 3 -1.8g / cm 3 (5) Based on the mass of the first negative electrode active material, the mass percentage of the artificial graphite B is 30%-90%, and can be selected as 40%-70%. The artificial graphite B meets at least one of the above conditions, which ensures the rate performance and helps to extend the storage life of the secondary battery.

[0011] In any embodiment, the secondary battery satisfies at least one of the following conditions: (1) the volume median particle size Dv50 of the second negative electrode active material is less than or equal to the volume median particle size Dv50 of the first negative electrode active material; optionally, the ratio of the volume median particle size Dv50 of the second negative electrode active material to the volume median particle size Dv50 of the first negative electrode active material is 0.5-1; (2) the particle size distribution (DV90-DV10) / DV50 of the second negative electrode active material is equal to the particle size distribution (DV90-DV10) / DV50 of the first negative electrode active material. The ratio of V90-DV10) / DV50 is 0.8-1.1; (3) the degree of graphitization of the second negative electrode active material is less than that of the first negative electrode active material; optionally, the ratio of the degree of graphitization of the second negative electrode active material to that of the first negative electrode active material is 0.95-0.99; (4) the specific surface area of ​​the second negative electrode active material is less than that of the first negative electrode active material; optionally, the ratio of the specific surface area of ​​the second negative electrode active material to that of the first negative electrode active material is 0.6m 2 / g-0.8m 2 / g; (5) The compacted density of the second negative electrode active material is less than the compacted density of the first negative electrode active material; optionally, the ratio of the compacted density of the first negative electrode active material to the compacted density of the first negative electrode active material is 0.6-0.95. A secondary battery that satisfies at least one of the above conditions is beneficial for simultaneously improving the storage performance and rate performance of the secondary battery.

[0012] In any embodiment, the second negative electrode active material comprises artificial graphite C, wherein the artificial graphite C comprises secondary particles and the surface of the artificial graphite C has an amorphous carbon coating layer; the mass ratio of the amorphous carbon coating layer to the artificial graphite C is 2%-8%, optionally 4%-6%. The second negative electrode material layer comprises artificial graphite C, and the amorphous carbon coating of the artificial graphite C facilitates lithium-ion intercalation, improving the rate performance of the secondary battery. Furthermore, under the synergistic effect of the first and second negative electrode material layers, the storage performance and rate performance of the secondary battery can be further improved.

[0013] In any embodiment, the second negative electrode active material comprises artificial graphite C, wherein the Dv50 of the artificial graphite C is less than the Dv50 of the artificial graphite A; optionally, the ratio of the Dv50 of the artificial graphite C to the Dv50 of the artificial graphite A is 0.5-1. By adjusting the ratio of the Dv50 of the artificial graphite C to the Dv50 of the artificial graphite A within the above range, it is beneficial to simultaneously improve the rate performance and safety performance of the secondary battery.

[0014] In any embodiment, the secondary battery satisfies at least one of the following conditions: (1) the ratio of the degree of graphitization of the artificial graphite C to that of the artificial graphite A is 0.95 to 1; (2) the ratio of the specific surface area of ​​the artificial graphite C to that of the artificial graphite A is 0.93 to 1; (3) the ratio of the compacted density of the artificial graphite A to that of the artificial graphite C powder is 1.01-1.3. Satisfying at least one of the above conditions is beneficial for simultaneously improving the storage performance and rate performance of the secondary battery.

[0015] In any embodiment, the compaction density of the first negative electrode material layer is greater than that of the second negative electrode material layer; the compaction density of the first negative electrode material layer is 1.6 g / cm³. 3 -1.8g / cm 3 The option is 1.6 g / cm³. 3 -1.75g / cm 3 The compaction density of the second negative electrode material layer is 1.3 g / cm³. 3 -1.6g / cm 3 The option is 1.4 g / cm³. 3 -1.6g / cm3 By adjusting the compaction density of the first and second negative electrode material layers within the aforementioned range, it is beneficial to fully utilize the high compaction of the first negative electrode active material and the high kinetic properties of the second negative electrode active material, thereby simultaneously improving the storage performance and rate performance of the secondary battery.

[0016] In any embodiment, the mass ratio of the first negative electrode material layer to the second negative electrode material layer is 2:3 to 3:2. By adjusting the mass ratio of the first negative electrode material layer to the second negative electrode material layer within the above range, it is beneficial to simultaneously improve the rate performance and storage performance of the secondary battery.

[0017] In any embodiment, both the first and second negative electrode active materials comprise silicon-based materials. The mass percentage of the silicon-based material is denoted as X based on the mass of the first negative electrode active material; the mass percentage of the silicon-based material is denoted as Y based on the mass of the second negative electrode active material. The secondary battery satisfies: X < Y; optionally, X ≤ 5%, and optionally, Y ≤ 10%. The introduction of silicon-based materials can increase the specific capacity of the first and second negative electrode active materials, thereby improving the energy density of the secondary battery. By controlling the mass percentage of silicon-based particles in the first and second negative electrode material layers within the above range, the rate performance can be guaranteed while further improving the energy density of the secondary battery.

[0018] A second aspect of this application provides an electrical device including a secondary battery selected from the second aspect of this application.

[0019] The beneficial effects of this application are: This application provides a secondary battery and an electrical device. The secondary battery includes a negative electrode sheet, which comprises a negative current collector, a first negative electrode material layer, and a second negative electrode material layer. The first negative electrode material layer is located between the negative current collector and the second negative electrode material layer. The first negative electrode material layer includes a first negative electrode active material, and the second negative electrode material layer includes a second negative electrode active material. By setting the first and second negative electrode material layers on the negative current collector and adjusting the first negative electrode active material in the first negative electrode material layer to include artificial graphite A and artificial graphite B, this application can simultaneously improve the energy density and rate performance of the secondary battery, as well as its longer service life. Of course, implementing any product or method of this application does not necessarily require achieving all of the above-described advantages simultaneously. Attached Figure Description

[0020] To more clearly illustrate the technical solutions of this application and the prior art, the accompanying drawings used in the embodiments and the prior art are briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application.

[0021] Figure 1 This is a cross-sectional structural diagram of the negative electrode sheet according to an embodiment of this application; Figure 2 This is a schematic diagram of a secondary battery according to one embodiment of this application; Figure 3 yes Figure 2 An exploded view of a secondary battery according to an embodiment of this application is shown; Figure 4 This is a schematic diagram of a battery module according to one embodiment of this application; Figure 5 This is a schematic diagram of a battery pack according to one embodiment of this application; Figure 6 yes Figure 5 An exploded view of a battery pack according to one embodiment of this application is shown; Figure 7 This is a schematic diagram of an electrical device that uses a secondary battery as a power source according to one embodiment of this application. Detailed Implementation

[0022] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the negative electrode, positive electrode, secondary battery, battery module, battery pack, and power-consuming device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0023] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0024] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0025] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0026] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, optionally sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0027] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0028] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0029] During the research process, the applicant discovered that while improving the kinetic performance (e.g., rate performance) of secondary batteries, the side reactions of the surface coatings often increase, leading to a shortened storage life or decreased cycle performance, making it difficult to meet the needs of practical applications. In order to simultaneously improve the storage and rate performance of secondary batteries, and enhance their overall performance, such as longer driving range and longer lifespan, this application provides a secondary battery and an electrical device.

[0030] It should be noted that, in the specific embodiments of this application, lithium-ion batteries are used as an example of secondary batteries to explain this application, but the secondary batteries in this application are not limited to lithium-ion batteries.

[0031] In one embodiment of this application, a secondary battery is proposed, the secondary battery including a negative electrode, such as... Figure 1 As shown, the negative electrode sheet includes a negative current collector 21, a first negative electrode material layer 22, and a second negative electrode material layer 23. The first negative electrode material layer 22 is located between the negative current collector 21 and the second negative electrode material layer 23. The first negative electrode material layer 22 includes a first negative electrode active material (not shown in the figure), and the second negative electrode material layer 23 includes a second negative electrode active material (not shown in the figure). The first negative electrode active material includes artificial graphite A and artificial graphite B. Artificial graphite A includes secondary particles and the surface of artificial graphite A has an amorphous carbon coating layer. Artificial graphite B includes primary particles and the surface of artificial graphite B does not have an amorphous carbon coating layer.

[0032] During the research process, the applicant discovered that by setting a first negative electrode material layer and a second negative electrode material layer on the negative electrode current collector, and by adjusting the first negative electrode active material in the first negative electrode material layer to make the first negative electrode active material include artificial graphite A and artificial graphite B, the rate performance of the secondary battery can be improved and the service life extended.

[0033] Without being limited to any particular theory, the applicant has discovered that the surface of artificial graphite A has an amorphous carbon coating layer, which increases the number of lithium-ion insertion sites and has a relatively large lattice spacing, resulting in faster lithium intercalation. This makes artificial graphite A beneficial for improving the rate performance of secondary batteries. Artificial graphite B has a regular graphite crystal structure with fewer structural defects and a high compaction density, which is beneficial for improving the energy density and lifespan of secondary batteries. Therefore, through the synergistic effect of artificial graphite A and artificial graphite B, the rate performance of secondary batteries can be improved while maintaining energy density, and the lifespan can be extended.

[0034] In some embodiments, the volumetric median particle size Dv50 of the first negative electrode active material is 13 μm-18 μm, optionally 15 μm-16 μm. The applicant has found that when the Dv50 of the first negative electrode active material is too small (e.g., less than 13 μm), the negative electrode active material is prone to side reactions with the electrolyte, causing irreversible losses and deteriorating the density of the first negative electrode material layer, thereby affecting the rate performance of the secondary battery. When the Dv50 of the first negative electrode active material is too large (e.g., greater than 18 μm), it easily affects the flatness of the first negative electrode material layer, thus affecting the safety performance of the secondary battery. By controlling the Dv50 value of the first negative electrode active material within the above-mentioned range, it is beneficial to simultaneously improve both rate performance and safety performance.

[0035] In some embodiments, the particle size distribution of the first negative electrode active material satisfies 1 ≤ (Dv90 - Dv10) / Dv50 ≤ 1.6, and optionally 1.1 ≤ (Dv90 - Dv10) / Dv50 ≤ 1.5. The applicant has found that by controlling the value of (Dv90 - Dv10) / Dv50 of the first negative electrode active material within the above range, it is beneficial to simultaneously improve rate performance and safety performance. This application does not impose any particular limitations on the Dv90 and Dv10 of the first negative electrode active material, as long as they meet the above particle size range. For example, the Dv90 of the first negative electrode active material is 24 μm-28 μm, and the Dv10 is 5 μm-12 μm.

[0036] In some embodiments, the graphitization degree of the first negative electrode active material is 92.8%-94.8%, optionally 93.5%-94.5%. The applicant has found that the graphitization degree reflects the regularity of the material's internal structure. When the graphitization degree of the first negative electrode active material is too low (e.g., below 92.8%), it indicates a high carbonization of artificial graphite A in the negative electrode active material, leading to increased side reactions during use, which in turn affects the storage and cycle life of the secondary battery. When the graphitization degree of the first negative electrode active material is too high (e.g., above 94.8%), the rate performance deteriorates, and the preparation difficulty and production cost of the first negative electrode active material increase. By controlling the graphitization degree of the first negative electrode active material within the above range, it is beneficial to improve the storage and rate performance of the secondary battery while controlling its cost.

[0037] In some embodiments, the specific surface area of ​​the first negative electrode active material is 1.0 m². 2 / g-1.6m 2 / g, can be selected as 1.05m 2 / g-1.3m 2 / g. The applicant discovered that when the specific surface area of ​​the first negative electrode active material is too small (e.g., less than 1.0 m²), 2 / g), which is not conducive to lithium ion insertion / extraction, thus affecting the rate performance of the secondary battery; when the specific surface area of ​​the first negative electrode active material is too large (e.g., greater than 1.6m²), it is also detrimental to lithium ion insertion / extraction, thus affecting the rate performance of the secondary battery; 2 The first negative electrode active material ( / g) is prone to side reactions with the electrolyte, causing irreversible losses and affecting the lifespan of the secondary battery. Controlling the specific surface area of ​​the first negative electrode active material within the aforementioned range is beneficial for improving the lifespan and rate performance of the secondary battery.

[0038] In some embodiments, the powder compaction density of the first negative electrode active material is 1.6 g / cm³. 3 -1.85g / cm 3 1.7 g / cm³ is an optional value. 3 -1.8g / cm 3 The applicant discovered that when the compacted density of the first negative electrode active material powder is too small (e.g., less than 1.6 g / cm³), 3 If the particles of the first negative electrode active material are not tightly packed together, the first negative electrode material layer is easily damaged during secondary battery cycling, affecting the service life of the secondary battery. Furthermore, if the powder compaction density of the first negative electrode active material is too high (e.g., greater than 1.85 g / cm³), it can also lead to problems. 3 The excessively dense packing of the particles in the first negative electrode active material hinders the lithium-ion insertion / extraction process, thus affecting the rate performance of the secondary battery. By controlling the powder compaction density of the first negative electrode active material within the aforementioned range, it is beneficial to improve the rate performance and extend the lifespan of the secondary battery. In this application, powder compaction density refers to the density of the corresponding material powder after treatment under 2T pressure.

[0039] In some embodiments, the volume median particle size Dv50 of the artificial graphite A is 14 μm-20 μm, optionally 16 μm-18 μm. The applicant has found that adjusting the Dv50 of the artificial graphite A within the above range is beneficial for improving the rate performance and safety performance of the secondary battery.

[0040] In some embodiments, the particle size distribution of artificial graphite A satisfies 0.8 ≤ (Dv90 - Dv10) / Dv50 ≤ 1.7, and optionally, 0.9 ≤ (Dv90 - Dv10) / Dv50 ≤ 1.4. The applicant has found that by controlling the value of (Dv90 - Dv10) / Dv50 of artificial graphite A within the above range, it is beneficial to improve the rate performance and safety performance of the secondary battery. This application does not impose any particular limitations on Dv90 and Dv10 of artificial graphite A, as long as they meet the above particle size range. For example, the Dv90 of artificial graphite A is 25 μm-27 μm, and the Dv10 is 7 μm-11 μm.

[0041] In some embodiments, the graphitization degree of artificial graphite A is 91.0%-92.8%, optionally 91.5%-92.5%. The applicant has found that by adjusting the graphitization degree of artificial graphite A within the above range, the lithium intercalation channels are moderate, and the secondary battery life will not be reduced too quickly due to excessive surface defects, thereby improving the lifespan and rate performance of the secondary battery and controlling its cost.

[0042] In some embodiments, the specific surface area of ​​artificial graphite A is 0.8 m². 2 / g-1.1 m 2 / g, optional 0.9m 2 / g-1m 2 / g. The applicant has discovered that by adjusting the specific surface area of ​​artificial graphite A within the above-mentioned range, the side reactions on the surface of artificial graphite A are kept within a reasonable range, which is beneficial to improving the service life of secondary batteries.

[0043] In some embodiments, the compacted density of the artificial graphite A powder is 1.5 g / cm³. 3 -1.8g / cm 3 1.6g / cm³ is an optional value. 3 -1.8 g / cm 3 Without being limited to any theory, the applicant has discovered that by adjusting the compaction density of graphite A powder within the aforementioned range, it is beneficial to increase the compaction difference between the first and second anode material layers, thereby improving the rate performance, cycle performance, and storage performance of the secondary battery.

[0044] In some embodiments, the mass ratio of the amorphous carbon coating layer in artificial graphite A to artificial graphite A is 1%-5%, optionally 3%-4%. The applicant has discovered that by adjusting the mass ratio of the amorphous carbon coating layer in artificial graphite A to artificial graphite A within the above range, the number of active sites in the first negative electrode active material is increased, which is beneficial for improving the rate performance of the secondary battery.

[0045] In some embodiments, the mass percentage of artificial graphite A is 10%-70%, optionally 30%-50%, based on the mass of the first negative electrode active material. The applicant has found that when the mass percentage of artificial graphite A is too low (e.g., below 10%), the content of artificial graphite B is too high, resulting in slow lithium intercalation of artificial graphite B and affecting the rate performance of the secondary battery. When the content of artificial graphite A is too high (e.g., above 70%), the content of artificial graphite B decreases, leading to deterioration of the lamination density of the first negative electrode material, increased surface defects, and a rise in side reactions, thus affecting the storage life and cycle performance of the secondary battery. By controlling the mass percentage of artificial graphite A within the aforementioned range, it is beneficial to simultaneously improve the rate performance, cycle performance, and storage performance of the secondary battery.

[0046] In some embodiments, the volume median particle size Dv50 of artificial graphite B is 12μm-16μm, optionally 15μm-16μm; the particle size distribution satisfies 0.5≤(Dv90-Dv10) / Dv50≤1.5; optionally, 0.7≤(Dv90-Dv10) / Dv50≤1.1. The applicant has found that by controlling the Dv50 and (Dv90-Dv10) / Dv50 values ​​of artificial graphite B within the above ranges, it is beneficial to improve the storage performance and safety performance of the secondary battery. This application does not impose any particular limitations on the Dv90 and Dv10 of artificial graphite B, as long as they meet the above particle size ranges. For example, the Dv90 of artificial graphite B is 25μm-30μm, and the Dv10 is 5μm-10μm.

[0047] In some embodiments, the graphitization degree of artificial graphite B is 93.5%-95.5%, optionally 94.0%-95.0%. The applicant has found that by adjusting the graphitization degree of artificial graphite B within the above range, there is less surface carbon impurities, which helps to improve the energy density of the secondary battery and control its cost while ensuring rate performance.

[0048] In some embodiments, the specific surface area of ​​artificial graphite B is 1.1 m². 2 / g-1.6m 2 / g, can be selected as 1.3m 2 / g-1.5m 2 / g. The applicant has discovered that adjusting the specific surface area of ​​artificial graphite B within the aforementioned range is beneficial for improving the storage performance of secondary batteries.

[0049] In some embodiments, the compacted density of the artificial graphite B powder is 1.6 g / cm³. 3 -1.85g / cm 3 1.6g / cm³ is an optional value. 3 -1.8g / cm 3The applicant has discovered that adjusting the compaction density of graphite B powder within the aforementioned range is beneficial for improving the storage performance of secondary batteries.

[0050] In some embodiments, the mass percentage of artificial graphite B is 30%-90%, optionally 40%-70%, based on the mass of the first negative electrode active material. The applicant has found that when the mass percentage of artificial graphite B is too low (e.g., below 30%), the content of artificial graphite A is too high, deteriorating the lamination density of the first negative electrode material and affecting the storage performance of the secondary battery; when the content of artificial graphite B is too high (e.g., above 90%), the content of artificial graphite A decreases, affecting the rate performance of the secondary battery. By controlling the mass percentage of artificial graphite B within the above range, it is beneficial to simultaneously improve the rate performance and storage performance of the secondary battery.

[0051] In some embodiments, the median volumetric particle size Dv50 of the second negative electrode active material in the secondary battery is less than or equal to the median volumetric particle size Dv50 of the first negative electrode active material. This allows for control over the compaction of the first and second negative electrode material layers, creating a compaction difference. The first negative electrode material layer has a higher compaction than the second material layer, which facilitates improved wettability of the electrolyte to the first negative electrode material layer. Optionally, the ratio of the median volumetric particle size Dv50 of the second negative electrode active material to that of the first negative electrode active material is 0.5-1. The applicant has found that by controlling the ratio of the median volumetric particle size Dv50 of the second negative electrode active material to be less than or equal to that of the first negative electrode active material within the above range, it is beneficial to ensure the compaction difference between the first and second negative electrode material layers, while simultaneously improving the rate performance and safety performance of the secondary battery. For example, the Dv50 of the second negative electrode active material can be 6.5 μm-18 μm.

[0052] In some embodiments, the particle size distribution (DV90-DV10) / DV50 of the second negative electrode active material in the secondary battery is different from that of the first negative electrode active material. V 90-D V 10) / D V The ratio of 50 is 0.8-1.1. The applicant discovered that by controlling the particle size distribution (D) of the second negative electrode active material... V 90-D V 10) / D V 50 and the particle size distribution of the first negative electrode active material (D V 90-D V 10) / D V A ratio of 50 within the above range is beneficial for simultaneously improving the rate performance and safety performance of secondary batteries.

[0053] In some embodiments, the graphitization degree of the second negative electrode active material in the secondary battery is lower than that of the first negative electrode active material, which can fully utilize the kinetic advantages of the second negative electrode active material. Optionally, the ratio of the graphitization degree of the second negative electrode active material to that of the first negative electrode active material is 0.95-0.99. The applicant has found that by adjusting the ratio of the graphitization degree of the second negative electrode active material to that of the first negative electrode active material within the above range, it is beneficial to improve the rate performance of the secondary battery and control its cost. For example, the graphitization degree of the second negative electrode active material can be 90%-92.12%.

[0054] In some embodiments, the specific surface area of ​​the second negative electrode active material in the secondary battery is smaller than that of the first negative electrode active material, which allows for reasonable control of the overall exposed area of ​​the negative electrode sheet. Optionally, the ratio of the specific surface area of ​​the second negative electrode active material to that of the first negative electrode active material is 0.6-0.8. The applicant has found that by adjusting the ratio of the specific surface area of ​​the second negative electrode active material to that of the first negative electrode active material within the above range, it is beneficial to improve the service life and rate performance of the secondary battery. For example, the specific surface area of ​​the second negative electrode active material can be 0.7 μm². 2 / g-1m 2 / g.

[0055] In some embodiments, the powder compaction density of the second negative electrode active material in the secondary battery is lower than that of the first negative electrode active material. This increases the compaction difference between the first and second negative electrode material layers, facilitating smoother passage of the electrolyte through the lower-density second negative electrode active material to the first negative electrode material layer, thus allowing the superior kinetic performance of the first negative electrode active material to be fully utilized. Optionally, the ratio of the powder compaction density of the second negative electrode active material to that of the first negative electrode active material is 0.6-0.95. The applicant has found that by controlling the ratio of the powder compaction density of the second negative electrode active material to that of the first negative electrode active material within the above range, it is beneficial to improve the rate performance, cycle performance, and storage performance of the secondary battery. For example, the powder tap density of the second negative electrode active material can be 1.3 g / cm³. 3 -1.65g / cm 3 .

[0056] In some embodiments, the second negative electrode active material includes artificial graphite C, which comprises secondary particles and has an amorphous carbon coating layer on its surface; the mass ratio of the amorphous carbon coating layer to the artificial graphite C is 2%-8%, optionally 4%-6%. The inclusion of artificial graphite C in the second negative electrode material layer is beneficial for improving the rate performance of the secondary battery, thereby further improving the storage performance and rate performance of the secondary battery through the synergistic effect of the first and second negative electrode material layers. The applicant has found that by controlling the mass ratio of the amorphous carbon coating layer to the artificial graphite C within the above-mentioned range, it is beneficial to improve the rate performance of the secondary battery.

[0057] In some embodiments, the second negative electrode active material includes artificial graphite C, where the Dv50 of artificial graphite C is less than that of artificial graphite A, enabling the second negative electrode material to have a lower lamination density than the first negative electrode material. Optionally, the ratio of the Dv50 of artificial graphite C to the Dv50 of artificial graphite A is 0.5-1. The applicant has found that by adjusting the ratio of the Dv50 of artificial graphite C to the Dv50 of artificial graphite A within the above range, it is beneficial to simultaneously improve the rate performance and safety performance of the secondary battery. For example, the Dv50 of artificial graphite C can be 7μm-13μm.

[0058] In some embodiments, the graphitization ratio of artificial graphite C to artificial graphite A in the secondary battery is 0.95-1. The applicant has found that by adjusting the graphitization ratio of artificial graphite C to artificial graphite A within the above range, it is beneficial to improve the storage performance and rate performance of the secondary battery while controlling its cost. For example, the graphitization degree of artificial graphite C can be 91%-92%.

[0059] In some embodiments, the ratio of the specific surface areas of artificial graphite C to artificial graphite A in the secondary battery is 0.93 to 1. The applicant has found that adjusting the ratio of the specific surface areas of artificial graphite C to artificial graphite A within the above range is beneficial to improving the rate performance of the secondary battery. For example, the specific surface area of ​​artificial graphite C can be 0.7 m². 2 / g-1.1m 2 / g.

[0060] In some embodiments, the ratio of the compacted density of artificial graphite A to artificial graphite C powder in the secondary battery is 1.01-1.3. The applicant has found that by controlling the ratio of the compacted density of artificial graphite A to artificial graphite C powder within the above range, it is beneficial to improve the rate performance, cycle performance, and storage performance of the secondary battery. For example, the compacted density of artificial graphite C powder can be 1.3 g / cm³. 3 -1.6g / cm 3 .

[0061] In some embodiments, the compaction density of the first negative electrode material layer is greater than that of the second negative electrode material layer. This allows the electrolyte to fully wet both layers, maximizing their performance and simultaneously improving the rate capability and energy density of the electrochemical device. The compaction density of the first negative electrode material layer is 1.6 g / cm³. 3 -1.8 g / cm 3 The optional value is 1.6 g / cm³. 3 -1.75 g / cm 3 The compaction density of the second negative electrode material layer is 1.3 g / cm³. 3 -1.6g / cm 3 1.4g / cm³ is an optional value. 3 -1.6g / cm 3 The applicant has discovered that by adjusting the compaction density of the first and second negative electrode material layers within the aforementioned range, it is beneficial to simultaneously improve the energy density and rate performance of the secondary battery.

[0062] In some embodiments, the mass ratio of the first negative electrode material layer to the second negative electrode material layer is 2:3 to 3:2. The applicant has found that when the mass ratio of the first negative electrode material layer to the second negative electrode material layer is too small (e.g., less than 2:3), meaning the first negative electrode material layer has a smaller mass and the second negative electrode material layer has a larger mass, it affects the storage life of the secondary battery. When the mass ratio of the first negative electrode material layer to the second negative electrode material layer is too large (e.g., greater than 3:2), meaning the first negative electrode material layer has a larger mass and the second negative electrode material layer has a smaller mass, it affects the rate performance of the secondary battery. By adjusting the mass ratio of the first negative electrode material layer to the second negative electrode material layer within the above range, it is beneficial to simultaneously improve the rate performance and energy density of the secondary battery.

[0063] In some embodiments, both the first and second negative electrode active materials comprise silicon-based materials. The mass percentage of the silicon-based material is denoted as X based on the mass of the first negative electrode active material; the mass percentage of the silicon-based material is denoted as Y based on the mass of the second negative electrode active material. The secondary battery satisfies: X < Y; optionally, X ≤ 5%, optionally, Y ≤ 10%, optionally X ≤ 2%, Y ≤ 6%. The introduction of silicon-based materials improves the specific capacity of either the first or second negative electrode active material, thereby increasing the energy density of the secondary battery. By controlling the mass percentage of silicon-based particles in the first and second negative electrode material layers within the aforementioned range, the energy density of the secondary battery can be further improved while maintaining rate performance.

[0064] In some embodiments, the first negative electrode active material may also include natural graphite.

[0065] This application does not impose any particular limitation on the preparation methods of artificial graphite A and artificial graphite C, as long as the purpose of this application can be achieved. For example, the preparation method may include, but is not limited to, the following steps: first, pre-treating the coke raw material to remove impurities, then pyrolyzing and granulating it to obtain secondary particles, then performing graphitization treatment, sieving and inspecting, coating the surface with pitch, and carbonizing at high temperature to obtain artificial graphite A or artificial graphite C. This application does not impose any particular limitation on the particle size of the secondary particles, as long as the purpose of this application can be achieved. For example, the volume median particle size (Dv50) of the secondary particles is 10 μm-20 μm. This application does not impose any particular limitation on the temperature and time of the above graphitization treatment, as long as the purpose of this application can be achieved. For example, the graphitization treatment temperature is 2400℃-3000℃, and the graphitization treatment time is 20h-30h. This application does not impose any particular limitation on the temperature and time of high-temperature carbonization, as long as the purpose of this application can be achieved. For example, the high-temperature carbonization temperature is 700℃-1500℃, and the high-temperature carbonization time is 7h-15h.

[0066] This application does not impose any particular limitation on the preparation method of artificial graphite B, as long as it achieves the purpose of this application. For example, the preparation method may include, but is not limited to, the following steps: the coke raw material is first pretreated to remove impurities, then pyrolyzed and granulated to obtain primary particles, then graphitized, and finally screened and inspected to obtain artificial graphite B. This application does not impose any particular limitation on the particle size of the primary particles, as long as it achieves the purpose of this application. For example, the volume median particle size (Dv50) of the primary particles is 12 μm-16 μm. This application does not impose any particular limitation on the temperature and time of the above graphitization treatment, as long as it achieves the purpose of this application. For example, the graphitization treatment temperature is 2400℃-3000℃, and the graphitization treatment time is 18h-30h.

[0067] The structure (e.g., core and coating) of the artificial graphite A or artificial graphite C in this application can be tested using equipment and methods known in the art. As an example, the following steps can be taken: Select a microgrid of a certain diameter (e.g., 3 mm), hold the edge of the microgrid with pointed tweezers, with the film side facing upwards (the side that appears glossy under light, i.e., the film side), and gently place it flat on white filter paper; take an appropriate amount of graphite particle sample (e.g., 1 g) and add it to a beaker containing an appropriate amount of ethanol, and sonicate for 10-30 minutes; use a glass capillary tube to aspirate, and then drop 2-3 drops of the sample onto the microgrid; after baking in an oven for 5 minutes, place the microgrid with the sample onto the sample stage, and test it using a transmission electron microscope (e.g., Hitachi HF-3300S Cs-corrected STEM) at a certain magnification (e.g., 60,000x) to obtain a transmission electron microscope (TEM) image of the sample. The core structure and coating structure can be observed from the TEM image.

[0068] In this application, Dv10, Dv50, and Dv90 are parameters well-known in the art and can be determined using a laser particle size analyzer (such as a Malvern Master Size 3000) with reference to the national standard GB / T19077-2016 (Laser Diffraction Method for Particle Size Distribution). Specifically, Dv10 refers to the particle size corresponding to a cumulative volume distribution percentage of 10%; Dv50 refers to the particle size corresponding to a cumulative volume distribution percentage of 50%; and Dv90 refers to the particle size corresponding to a cumulative volume distribution percentage of 90%.

[0069] The degree of graphitization in this application has a meaning known in the art and can be tested using methods known in the art. For example, an X-ray diffractometer (e.g., Bruker D8 Discover) can be used, and the testing methods refer to standards JIS K 0131-1996 (General Rules for Measurement and Analysis by X-ray Diffractometer), JB / T 4220-2011 (Methods for Determination of Lattice Parameters of Artificial Graphite), and GB / T 24533-2019 (Graphite Anode Materials for Lithium-ion Batteries). Specifically, the d002 value of the material is first measured, and then the degree of graphitization (G) is calculated according to the formula (0.344-d002) / (0.344-0.3354)×100%, to obtain the degree of graphitization of the measured material, where d002 refers to the interlayer spacing in the graphite crystal structure, with the unit being nm. In X-ray diffraction analysis, a copper target can be used as the anode target, with CuKα rays as the radiation source. The ray wavelength is λ=1.5418Å, the scanning 2θ angle range is 20°-80°, and the scanning rate can be 4° / min.

[0070] Specific surface area in this application has a meaning known in the art and can be tested using methods known in the art. For example, it can be tested using the nitrogen adsorption specific surface area analysis method according to the national standard GB / T 19587-2017 (Determination of Specific Surface Area of ​​Solid Substances by Gas Adsorption BET Method) and calculated using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis can be performed using the Tri-Star 3020 specific surface area and pore size analyzer from Micromeritics, Inc., USA.

[0071] The term "powder compaction density" in this application has a well-known meaning in the art and can be tested using methods known in the art. For example, it can be tested using an electronic pressure testing machine (such as UTM7305) with reference to the national standard GB / T 24533-2009 ("Graphite Anode Materials for Lithium-ion Batteries"): Place the powder sample to be tested with a mass of M on a compaction mold (bottom area S), set different pressures (2T can be used in this application), hold the pressure for 30s, release the pressure, wait for 10s, read the thickness H of the powder after compaction under that pressure on the equipment, and calculate the powder compaction density under that pressure: Powder compaction density = M / (H×S).

[0072] In addition, the secondary battery and power supply device of this application, as well as the battery module and battery pack containing the secondary battery of this application, will be described below with appropriate reference to the accompanying drawings.

[0073] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and releasing. The electrolyte acts as a conductor between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.

[0074] [Positive electrode plate] The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector. As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0075] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0076] In some embodiments, the positive electrode active material may be a known battery positive electrode active material. As an example, the positive electrode active material may include at least one of the following materials: lithium phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as battery positive electrode active materials may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also known as NCM) 333 LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM) 523 LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811 ), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.15 Al 0.05 At least one of O2 and its modified compounds. Examples of lithium phosphates with an olivine structure include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.

[0077] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0078] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0079] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0080] [Negative electrode plate] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and a first negative electrode material layer and a second negative electrode material layer are disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0081] In some embodiments, the negative current collector of the negative electrode sheet may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0082] In some embodiments, the first negative electrode material layer and the second negative electrode material layer may optionally include an adhesive. The adhesive may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0083] In some embodiments, the first negative electrode material layer and the second negative electrode material layer may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0084] In some embodiments, the first negative electrode material layer and the second negative electrode material layer may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0085] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the first negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a first negative electrode slurry; dispersing the second negative electrode active material, conductive agent, binder and any other components in a solvent (e.g., deionized water) to form a second negative electrode slurry; coating the first negative electrode slurry onto the negative electrode current collector, and drying it to obtain a negative electrode current collector containing a first negative electrode material layer; then coating the second negative electrode slurry onto the first negative electrode material layer, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0086] [Electrolytes] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.

[0087] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.

[0088] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0089] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0090] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.

[0091] [Isolation membrane] In some embodiments, the secondary battery also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0092] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0093] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.

[0094] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the aforementioned electrode assembly and electrolyte.

[0095] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft pack, such as a pouch. The material of the soft pack can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0096] This application does not impose any particular limitation on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 2 This is an example of a square-structured secondary battery 5.

[0097] In some implementations, refer to Figure 3 The outer packaging may include a housing 51 and a cover plate 53. The housing 51 may include a bottom plate and side plates connected to the bottom plate, the bottom plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 can be placed over the opening to close the receiving cavity. The positive electrode, negative electrode, and separator can be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. ​​The secondary battery 5 may contain one or more electrode assemblies 52, which can be selected by those skilled in the art according to specific practical needs.

[0098] In some implementations, the secondary batteries can be assembled into a battery module, and the number of secondary batteries contained in the battery module can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery module.

[0099] Figure 4 This is battery module 4, used as an example. (See reference...) Figure 4 In battery module 4, multiple secondary batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple secondary batteries 5 can be fixed in place using fasteners.

[0100] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of secondary batteries 5 are received.

[0101] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0102] Figure 5 and Figure 6 This is a sample battery pack 10. (See reference...) Figure 5 and Figure 6 The battery pack 10 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper box 11 and a lower box 12, with the upper box 11 covering the lower box 12 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0103] In addition, this application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in this application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0104] As the electrical device, a secondary battery, battery module, or battery pack can be selected according to its usage requirements.

[0105] Figure 7 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery for this device, a battery pack or battery module can be used.

[0106] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a rechargeable battery as their power source.

[0107] Example The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0108] Example 1-1 <Preparation of the positive electrode> LiNi, the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2, conductive carbon black (conductive agent), and polyvinylidene fluoride (PVDF) (binder) were mixed in a mass ratio of 98:1:1. N-methylpyrrolidone (NMP) was then added as a solvent, and the mixture was stirred under vacuum until homogeneous, yielding a positive electrode slurry with a solid content of 75 wt%. The positive electrode slurry was uniformly coated onto one surface of a 13 µm thick aluminum foil, dried at 90 °C, and cold-pressed to obtain a positive electrode sheet with a positive active material layer thickness of 114 µm. This positive electrode sheet was then obtained through processes such as tab forming and slitting.

[0109] <Preparation of Negative Electrode Active Materials> Artificial Graphite A: Coke raw material is first pretreated to remove impurities, then pyrolyzed and granulated to obtain secondary particles with a Dv50 of 15 μm. These particles are then graphitized at 3000℃ for 24 hours, coated with pitch, and carbonized at 800℃ for 10 hours to obtain artificial graphite A. Artificial graphite A has a Dv50 of 16 μm, a Dv90 of 26 μm, a Dv10 of 7 μm, a graphitization degree of 92.5%, and a specific surface area of ​​0.9 m². 2 / g, the compacted density of the powder is 1.7g / cm³. 3 The mass ratio of the coating layer in artificial graphite A to artificial graphite A is 3%.

[0110] Artificial graphite B: The coke raw material is first pretreated to remove impurities, then pyrolyzed and granulated to obtain primary particles with a Dv50 of 14μm, and then graphitized at 2800℃ for 20h to obtain artificial graphite B.

[0111] Artificial graphite C: The coke raw material is first pretreated to remove impurities, then pyrolyzed and granulated to obtain secondary particles with a Dv50 of 10 μm. These particles are then graphitized at 3000℃ for 24 hours, coated with pitch, and carbonized at 1000℃ for 15 hours. The artificial graphite C has a Dv50 of 12 μm, a Dv90 of 20 μm, a Dv10 of 6.5 μm, a graphitization degree of 91.8%, and a specific surface area of ​​0.86 m². 2 / g, the compacted density of the powder is 1.6g / cm³. 3The mass ratio of the coating layer in artificial graphite C to the mass of artificial graphite C is 5%.

[0112] <Preparation of Negative Electrode Sheets> Preparation of the first negative electrode slurry: Artificial graphite A and artificial graphite B were mixed at a mass ratio of 1:9 to obtain the first negative electrode active material (artificial graphite A accounted for 10% of the mass). The first negative electrode active material, conductive carbon black (conductive agent), carboxymethyl cellulose (CMC), and binder SBR were mixed at a mass ratio of 96.8:0.8:1.2:1.2. Deionized water was added as a solvent, and the mixture was stirred under vacuum until homogeneous, yielding a first negative electrode slurry with a solid content of 66 wt%. The first negative electrode active material had a Dv50 of 15 μm, a Dv90 of 25 μm, a Dv10 of 5.7 μm, a graphitization degree of 94%, and a specific surface area of ​​1.2 m². 2 / g, the compacted density of the powder is 1.7g / cm³. 3 .

[0113] Preparation of the second negative electrode slurry: Artificial graphite C (the second negative electrode active material), conductive carbon black (the conductive agent), carboxymethyl cellulose (CMC), and SBR (the binder) were mixed in a mass ratio of 96.8:0.8:1.1:1.3. Deionized water was added as a solvent, and the mixture was stirred under vacuum until homogeneous, yielding a second negative electrode slurry with a solid content of 66 wt%. The second negative electrode active material exhibited a Dv50 of 12 μm, a Dv90 of 20 μm, a Dv10 of 6.5 μm, a graphitization degree of 91.8%, and a specific surface area of ​​0.86 m². 2 / g, the compacted density of the powder is 1.6g / cm³. 3 .

[0114] A first negative electrode slurry is coated onto one surface of an 8µm thick copper foil current collector, and after drying, a negative electrode current collector containing a first negative electrode material layer is obtained. Then, a second negative electrode slurry is coated onto the first negative electrode material layer, and after drying at 110℃, a negative electrode current collector containing both a first and a second negative electrode material layer is obtained. The above steps are repeated on the other surface of the negative electrode current collector, and after cold pressing, a negative electrode sheet with a first negative electrode active material layer thickness of 54µm and a second negative electrode active material layer thickness of 81µm is obtained. This negative electrode sheet is then processed through tab forming and slitting to obtain the final negative electrode sheet. The mass ratio of the first to the second negative electrode material layer is 2:3, and the compaction density of the first negative electrode material layer is 1.7 g / cm³. 3 The compaction density of the second negative electrode material layer is 1.6 g / cm³. 3 The compaction density of the negative electrode sheet is 1.65 g / cm³. 3 .

[0115] <Preparation of Electrolyte> In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate are mixed in a volume ratio of 1:1:1 to obtain an electrolyte solvent. Then, lithium salt LiPF6 is dissolved in the mixed solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0116] <Preparation of the separating membrane> Polyethylene film is selected as the separator. Before use, it is cut to the appropriate size according to the size of the positive and negative electrode plates.

[0117] <Preparation of Lithium-ion Batteries> The positive electrode, separator, and negative electrode are stacked in sequence, with the separator acting as a separator between the positive and negative electrodes. The electrode assembly is then wound up. The electrode assembly is placed in an outer packaging shell, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping, a lithium-ion battery is obtained.

[0118] Examples 1-2 to 1-4 are the same as in Example 1-1, except that the mass percentages of artificial graphite A and artificial graphite B are adjusted as shown in Table 1.

[0119] Examples 2-1 to 2-4 are the same as in Example 2-1, except that the Dv50 of the first negative electrode active material, artificial graphite A and artificial graphite B are adjusted as shown in Table 2.

[0120] Examples 3-1 to 3-4 are the same as in Example 3-1, except that the graphitization degree of the first negative electrode active material, artificial graphite A, and artificial graphite B is adjusted according to Table 3.

[0121] Examples 4-1 to 4-4 are the same as in Example 4-1, except that the graphitization degree of the first negative electrode active material, artificial graphite A, and artificial graphite B is adjusted according to Table 4.

[0122] Examples 5-1 to 5-4 are the same as in Example 5-1, except that the graphitization degree of the first negative electrode active material, artificial graphite A, and artificial graphite B is adjusted according to Table 5.

[0123] Examples 6-1 to 6-4 are the same as in Example 6-1, except that the ratio of the second negative electrode active material Dv50 to the first negative electrode active material Dv50 and the Dv50 of the first and second negative electrode active materials are adjusted as shown in Table 6.

[0124] Examples 7-1 to 7-4 are the same as in Example 1-1, except that the ratio of the graphitization degree of the second negative electrode active material to that of the first negative electrode active material and the graphitization degree of the first and second negative electrode active materials are adjusted according to Table 7.

[0125] Examples 8-1 to 8-4 are the same as Example 1-1, except that the values ​​of X and Y are adjusted as shown in Table 8.

[0126] Comparative Examples 1-1 and 1-2 were identical to Example 1-1, except that the mass percentages of artificial graphite A and artificial graphite B were adjusted as shown in Table 1.

[0127] Comparative Examples 2-1 and 2-2 were identical to Example 2-1, except that the Dv50 of the first negative electrode active material, artificial graphite A, and artificial graphite B were adjusted as shown in Table 2.

[0128] Comparative Examples 3-1 and 3-2 were identical to Example 3-1, except that the graphitization degree of the first negative electrode active material, artificial graphite A, and artificial graphite B was adjusted as shown in Table 3.

[0129] Comparative Examples 4-1 and 4-2 were identical to Example 4-1, except that the graphitization degree of the first negative electrode active material, artificial graphite A, and artificial graphite B was adjusted as shown in Table 4.

[0130] Comparative Examples 5-1 and 5-2 were identical to Example 5-1, except that the graphitization degree of the first negative electrode active material, artificial graphite A, and artificial graphite B was adjusted as shown in Table 5.

[0131] Comparative Examples 6-1 and 6-2 are the same as in Example 6-1, except that the ratio of the second negative electrode active material Dv50 to the first negative electrode active material Dv50 and the Dv50 of the first and second negative electrode active materials are adjusted as shown in Table 6.

[0132] Comparative Examples 7-1 and 7-2 are the same as in Example 7-4, except that the ratio of the graphitization degree of the second negative electrode active material to that of the first negative electrode active material and the graphitization degree of the first and second negative electrode active materials are adjusted as shown in Table 7.

[0133] Comparative Examples 8-1 and 8-2 are the same as Example 1-1, except that the values ​​of X and Y are adjusted as shown in Table 8.

[0134] The lithium-ion batteries prepared in the above embodiments and comparative examples were subjected to the following performance tests. The preparation parameters and performance data of each embodiment are shown in Tables 1-8.

[0135] Charging capability test: At 25°C, the lithium-ion batteries prepared in the examples and comparative examples were fully charged at nC (e.g., n=0.1, 0.2, 0.3, 0.4, 0.5) and fully discharged at 1C. This cycle was repeated 10 times. Then, the lithium-ion batteries were fully charged at 1C. The negative electrode was then disassembled to observe the lithium deposition on the surface of the negative electrode. If no lithium deposition was observed, the batteries were fully charged at (n+0.1)C and the test was repeated. This process was repeated until lithium deposition occurred on the surface of the negative electrode. The maximum charging capacity of the lithium-ion battery was obtained by subtracting 0.1C from the current charging rate.

[0136] Energy density (W) test: At 25℃, the battery is fully charged at a rate of 0.33C and fully discharged at a rate of 0.33C for 3 cycles. The discharge energy (E) of the last cycle is recorded, and the mass (m) of the lithium-ion battery is weighed using an electronic balance. W=E / m.

[0137] Storage life test: The battery was fully charged to 97% state of charge (SOC) and stored at 60°C until its capacity decreased to 80%. The storage time at this point was recorded. The target storage time was 280 days. The ratio of the actual and comparative examples to the target storage time was calculated and recorded as the storage lifetime. The target storage lifetime was 100%.

[0138] Cyclic performance test: At 25°C, the lithium-ion batteries prepared in the examples and comparative examples were charged at a 3C rate and discharged at a 1C rate, undergoing a 3%-97% SOC cycle test until the capacity of the lithium-ion batteries was less than 80% of the initial capacity. The number of cycles was recorded, with a target number of 2000 cycles. The ratio of the target cycle time to the cycle time of the examples and comparative examples was calculated and recorded as the cycle performance. The target cycle life was 100%.

[0139] Table 1

[0140] Note: " / " in Table 1 indicates that the corresponding parameter or substance does not exist.

[0141] Table 2

[0142] Table 3

[0143] Table 4

[0144] Table 5

[0145] Table 6

[0146] Table 7

[0147] Table 8

[0148] Referring to Table 1, it can be seen from Examples 1-1 to 1-4, Comparative Examples 1-1 and 1-2 that when the negative electrode sheet of the lithium-ion battery includes a first negative electrode material layer and a second negative electrode material layer, and the first negative electrode material layer includes both artificial graphite A and artificial graphite B, and the second negative electrode material layer includes artificial graphite C, the lithium-ion battery obtained by utilizing the high kinetics of artificial graphite A and artificial graphite C, as well as the high storage performance of artificial graphite C, has a longer storage life and a higher charging rate, that is, it has good comprehensive performance.

[0149] As can be seen from Examples 1-1 to 1-4, Comparative Examples 1-3 and 1-4, when the mass percentage of artificial graphite A is outside the range specified in this application, it is difficult to simultaneously achieve good storage life and rate performance of the lithium-ion battery, and its overall performance is inferior to that of the lithium-ion batteries obtained in the examples. When the mass percentage of artificial graphite A is within the range specified in this application, the resulting lithium-ion battery exhibits better overall performance.

[0150] Referring to Table 2, it can be seen from Examples 2-1 to 2-4, Comparative Examples 2-1 and 2-2 that when the Dv50 of the first negative electrode active material is within the scope of this application, the resulting lithium-ion battery has better overall performance.

[0151] Referring to Table 3, it can be seen from Examples 3-1 to 3-4, Comparative Examples 3-1 and 3-2 that when the graphitization of the first negative electrode active material is too low, although the rate performance of the lithium-ion battery is slightly improved, the storage life deteriorates; when the graphitization of the first negative electrode active material is too high, it affects the rate performance of the lithium-ion battery. When the graphitization of the first negative electrode active material is within the range of this application, it is beneficial to balance the rate performance and storage life of the lithium-ion battery, resulting in a lithium-ion battery with better overall performance.

[0152] Referring to Tables 4 and 5, it can be seen from Examples 4-1 to 4-4, Comparative Examples 4-1 and 4-2 that when the graphitization degree of artificial graphite B remains constant, and the graphitization degree of artificial graphite A is within the range of this application, the resulting lithium-ion battery exhibits better overall performance. It can also be seen from Examples 5-1 to 5-4, Comparative Examples 5-1 and 5-2 that when the graphitization degree of artificial graphite A remains constant, and the graphitization degree of artificial graphite B is within the range of this application, the resulting lithium-ion battery exhibits better overall performance. Furthermore, it can be seen that the graphitization degree of artificial graphite A mainly affects the rate performance of the lithium-ion battery, while the graphitization degree of artificial graphite B mainly affects the storage life of the lithium-ion battery.

[0153] Referring to Table 6, it can be seen from Examples 6-1 to 6-4, Comparative Examples 6-1 and 6-2 that when the ratio of the second negative electrode active material Dv50 to the first negative electrode active material Dv50 is too large, it will affect the rate performance of the lithium-ion battery; when the ratio of the second negative electrode active material Dv50 to the first negative electrode active material Dv50 is too small, it will affect both the rate performance and storage performance of the lithium-ion battery. When the ratio of the second negative electrode active material Dv50 to the first negative electrode active material Dv50 is within the range of this application, the resulting lithium-ion battery has better overall performance.

[0154] Referring to Table 7, it can be seen from Examples 7-1 to 7-4, Comparative Examples 7-1 and 7-2 that when the ratio of the graphitization degree of the second negative electrode active material to that of the first negative electrode active material is too small, it will affect the storage life of the lithium-ion battery; when the ratio of the graphitization degree of the second negative electrode active material to that of the first negative electrode active material is too large, it will affect the rate performance of the lithium-ion battery. When the ratio of the graphitization degree of the second negative electrode active material to that of the first negative electrode active material is within the range of this application, the resulting lithium-ion battery has better overall performance.

[0155] Referring to Table 8, it can be seen from Examples 8-1 to 8-4, Comparative Examples 8-1 and 8-2 that when both the first and second negative electrode active materials include silicon-based materials, and the mass percentage of silicon-based materials is within the range of this application, the resulting lithium-ion battery exhibits good overall performance. It can also be seen from Examples 8-1 to 8-4 that when the second negative electrode active material includes silicon-based materials and the first negative electrode active material does not, it is more beneficial to improve the overall performance of the lithium-ion battery.

[0156] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A secondary battery comprising a negative electrode sheet, the negative electrode sheet comprising a negative current collector, a first negative electrode material layer, and a second negative electrode material layer, the first negative electrode material layer being located between the negative current collector and the second negative electrode material layer, the first negative electrode material layer comprising a first negative electrode active material, and the second negative electrode layer comprising a second negative electrode active material, wherein... The first negative electrode active material includes artificial graphite A and artificial graphite B. The artificial graphite A includes secondary particles and the surface of the artificial graphite A has an amorphous carbon coating layer. The artificial graphite B includes primary particles and the surface of the artificial graphite B does not have an amorphous carbon coating layer. The first negative electrode active material and / or the second negative electrode active material include silicon-based materials.

2. The secondary battery according to claim 1, characterized in that, The first negative electrode active material satisfies at least one of the following conditions: (1) The volume median particle size Dv50 is 13μm-18μm, and can be selected as 15μm-16μm; (2) The particle size distribution satisfies: 1≤(Dv90-Dv10) / Dv50≤1.6, which can be selected as 1.1≤(Dv90-Dv10) / Dv50≤1.5; (3) The degree of graphitization is 92.8%-94.8%, and can be selected as 93.5%-94.5%; (4) Specific surface area is 1.0 m² 2 / g-1.6 m 2 / g, can be selected as 1.05m 2 / g-1.3 m 2 / g; (5) The compacted density of the powder is 1.6 g / cm³. 3 -1.85g / cm 3 1.7g / cm³ is an optional value. 3 -1.8g / cm 3 .

3. The secondary battery according to claim 1 or 2, characterized in that, The artificial graphite A satisfies at least one of the following conditions: (1) The volume median particle size Dv50 is 14μm-20μm, and can be selected as 16μm-18μm; (2) The particle size distribution satisfies: 0.8≤(Dv90-Dv10) / Dv50≤1.7, and optionally, 0.9≤(Dv90-Dv10) / Dv50≤1.4; (3) The degree of graphitization is 91.0%-92.8%, and can be selected as 91.5%-92.5%; (4) Specific surface area is 0.8 m² 2 / g-1.1 m 2 / g, optional 0.9m 2 / g-1m 2 / g; (5) The compacted density of the powder is 1.5 g / cm³. 3 -1.8g / cm 3 1.6m is optional. 2 / g-1.8m 2 / g; (6) Based on the mass of the first negative electrode active material, the mass percentage of the artificial graphite A is 10%-70%, and can be selected as 30%-50%; (7) The mass ratio of the amorphous carbon coating layer in the artificial graphite A to the artificial graphite A is 1%-5%, and can be selected as 3%-4%.

4. The secondary battery according to any one of claims 1-3, characterized in that, The artificial graphite B satisfies at least one of the following conditions: (1) The median particle size Dv50 is 12μm-16μm, and can be selected as 15μm-16μm; the particle size distribution satisfies 0.5≤(Dv90-Dv10) / Dv50≤1.5; preferably, 0.7≤(Dv90-Dv10) / Dv50≤1.1; (2) The degree of graphitization is 93.5%-95.5%, preferably 94.0%-95.0%; (3) Specific surface area is 1.1m² 2 / g-1.6m 2 / g, preferably 1.3m 2 / g-1.5m 2 / g; (4) The compacted density of the powder is 1.6 g / cm³. 3 -1.85g / cm 3 The preferred value is 1.6 g / cm³. 3 -1.8g / cm 3 ; (5) Based on the mass of the first negative electrode active material, the mass percentage of the artificial graphite B is 30%-90%, and can be selected as 40%-70%.

5. The secondary battery according to any one of claims 1-4, characterized in that, The secondary battery satisfies at least one of the following conditions: (1) The volume median particle size Dv50 of the second negative electrode active material is less than or equal to the volume median particle size Dv50 of the first negative electrode active material; preferably, the ratio of the volume median particle size Dv50 of the second negative electrode active material to the volume median particle size Dv50 of the first negative electrode active material is 0.5-1. (2) The ratio of the particle size distribution (DV90-DV10) / DV50 of the second negative electrode active material to the particle size distribution (DV90-DV10) / DV50 of the first negative electrode active material is 0.8-1.1; (3) The degree of graphitization of the second negative electrode active material is less than that of the first negative electrode active material; optionally, the ratio of the degree of graphitization of the second negative electrode active material to that of the first negative electrode active material is 0.95-0.99; (4) The specific surface area of ​​the second negative electrode active material is smaller than that of the first negative electrode active material; optionally, the ratio of the specific surface area of ​​the second negative electrode active material to that of the first negative electrode active material is 0.6 to 0.

8. (5) The compacted density of the second negative electrode active material is less than that of the first negative electrode active material; optionally, the ratio of the compacted density of the second negative electrode active material to that of the first negative electrode active material is 0.67-0.

95.

6. The secondary battery according to any one of claims 1-5, characterized in that, The second negative electrode active material includes artificial graphite C, which comprises secondary particles and has an amorphous carbon coating layer on its surface; the mass ratio of the amorphous carbon coating layer to the artificial graphite C is 2%-8%.

7. The secondary battery according to claim 6, characterized in that, The second negative electrode active material includes artificial graphite C, wherein the Dv50 of artificial graphite C is less than the Dv50 of artificial graphite A; optionally, the ratio of the Dv50 of artificial graphite C to the Dv50 of artificial graphite A is 0.5-1.

8. The secondary battery according to any one of claims 6-7, characterized in that, The secondary battery satisfies at least one of the following conditions: (1) The ratio of the degree of graphitization of the artificial graphite C to that of the artificial graphite A is 0.95-1; (2) The ratio of the specific surface area of ​​the artificial graphite C to that of the artificial graphite A is 0.93-1; (3) The ratio of the compacted density of the artificial graphite A to that of the artificial graphite C powder is 1.01-1.

3.

9. The secondary battery according to any one of claims 1-8, characterized in that, The compaction density of the first negative electrode material layer is greater than that of the second negative electrode material layer; The compaction density of the first negative electrode material layer is 1.6 g / cm³. 3 -1.8g / cm 3 The option is 1.6 g / cm³. 3 -1.75 g / cm 3 ; The compaction density of the second negative electrode material layer is 1.3 g / cm³. 3 -1.6g / cm 3 The option is 1.4 g / cm³. 3 -1.6 g / cm 3 .

10. The secondary battery according to any one of claims 1-9, characterized in that, The mass ratio of the first negative electrode material layer to the second negative electrode material layer is 2:3 to 3:

2.

11. The secondary battery according to any one of claims 1-10, characterized in that, Both the first negative electrode active material and the second negative electrode active material include silicon-based materials. The mass percentage of the silicon-based material is denoted as X based on the mass of the first negative electrode active material; the mass percentage of the silicon-based material is denoted as Y based on the mass of the second negative electrode active material. The secondary battery satisfies: X < Y; Optionally, X ≤ 5%; Optionally, Y ≤ 10%.

12. An electrical device comprising a secondary battery as described in any one of claims 1-11.